Perception of Pre-School Teachers on the Role of Music and Movement in the Learning in Public Pre-school in Muhoroni Sub County ,Kenya - Ondiek, Atieno Dolphine (JOOUST, 2015)
Most governments from developing countries have education policies that do not lay emphasis on the use of music and movement for teaching ECDE learners. Despite the Kenyan government policy requiring that music and movement be incorporated in all activity areas, the emphasis of this implementation has not been realized. This has prevented most class one entrants from pre-schools the requisite listening and communicating skills. The purpose of this study was to investigate the perception of pre - school teachers on the role of music and movement in the learning of ECDE learners in Muhoroni Sub County. This descriptive research design was framed from Gardner's Multiple Intelligence theory, with the objectives being to determine the perception of pre-school teachers on the role of songs in the learning of ECDE learners, to establish the perception of pre-school teachers on the role of sound sensitivity in the learning of ECDE learners, to ascertain the perception of pre-school teachers on the role of dance in the learning of ECDE learners, and to find out the challenges faced in implementing music and movement in the learning of ECDE learners. The accessible population of this study comprised of 315 pre-school teachers from 105 public pre-schools and 12 education officers from Muhoroni Sub County education office, whereby 97 schools were sampled for the study and the remaining 8 schools used for piloting. Simple random sampling was used to select 126 pre-school teachers, while purposive sampling was used to select 8 education officers to be used as key informants. Questionnaires and interview schedules were used for data collection, and reliability and validity of the instruments were ensured through Split-Half and expert consultations with the departmental supervisors, respectively. Trustworthiness of interview schedule was ensured by verifying research steps through examination of raw data, data reduction products, and process notes during interviews. Qualitative data obtained from interviews and open ended questions were grouped into themes corresponding with the study objectives and used to validate data obtained in questionnaires on one hand, while quantitative data were coded and analyzed by use of SPSS computer package. It was found that singing helps in the social development of ECDE learners; sound identification assists ECDE learners to learn names of animals, machines, dancing aids in the physical development of ECDE learners, and that the most outstanding challenge facing the implementation of music and movement in ECDE learning is the inability of parents to pay fees capable for acquiring musical instruments. The researcher recommends that parents should be encouraged to allow ECDE learners to participate in singing, verse citing, and dancing sessions while at home and in school, and enough free space should be created for the children for this purpose. Similarly, the government should provide free ECDE to learners to ease the difficulties faced in the acquisition of music instruments. Similarly, further studies should be done on the influence of parents in the implantation of music and movement, and the perception of pre-school teachers on how cultural inclinations portend on the use of music and movement in the learning of ECDE learners.